Superman. Volume 2, Return to glory - Huder, Aaron; Pak, Greg; Tomasi, Peter; Yang, Gene Luen (DC Comics, 2016)
"Superman is forced to join a super-fight club--and the stakes couldn't be higher. The Man of Steel must make a fateful choice. Can he risk exposing himself to the one thing that could save him? Later, Superman and Wonder Woman lead an army of gods and monsters against Vandal Savage and his deadly spawn!"--